Analisis Penerapan PSAK No.24 (Revisi 2013) tentang Imbalan Kerja pada PT. XYZ - Auliffi Ermian Challen (Lembaga Penelitian Universitas YARSI, 2019)
The purpose of this study is to determine the difference between SFAS 24 revision 2013 and SFAS no 24 revised 2010, as well as the impact of the application of SFAS no 24 revision 2013 on the Company's Financial Statement of PT XYZ with the difference calculation by independent actuaries. The research was conducted by descriptive method through case study approach at PT XYZ with data collection method, and analysis of document obtained from company. The results of this study indicate that there is a difference between PSAK No. 24 revised 2010 and PSAK no 24 revision 2013. The difference is the acknowledgment of actuarial gains/losses, the components of the post-employment benefits expenses, and the components of the post-employment liabilities obligations (liabilities). Thus, the adoption of PSAK No. 24 revision 2013, provides an impact on the need to reevaluate the post-employment benefits and post-employment benefits obligations (liabilities) benefits by an independent actuaries. This application leads to a restatement of the post-employment benefits fee and post-employment liability (liabilities) obligations. The balance of post-employment benefits expense decreased and post-employment liabilities liabilities increased significantly.